Monetary policy as a mechanism to combat inflation in Algeria during the period (2000-2014) - Abdel latif haddadi; Ilyas Saleh (Dirassat Journal Economic Issue, 2016)
This study (research) try to high light on a global phenomenon has a huge impact on international economy, including, the developed and developing countries, this case is « inflation » the reasons of the case are related to the Skuctural Disruption in the public Economic policies to countries , which the monetary policy is represents most important, considering that the Inflation has a strong relation with the Amount of money and general level of price ,then, any change in that tow last variables, if the orther variables are constant that will be affect on the phenomenon of study Algerian economy has dependency to the foreign countries also it depends on an ail exports, Algerian economy is among the most economies, is affected by an increase of prices, so as it’s interaction with internal and external factors of the environment, this study aimed to know, how the effectiveness of the monetary policy in Algeria to face an inflation problems.